2016
DOI: 10.1155/2016/5128720
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibody Response to ZRF1 and KRR1 SEREX Antigens in Patients with Breast Tumors of Different Histological Types and Grades

Abstract: Purpose. To investigate a frequency of antibody response to SEREX-identified medullary breast carcinoma autoantigens ZRF1 and KRR1 in sera of breast cancer patients taking into account clinical and molecular characteristics of tumors for opening of new perspectives in creation of minimally invasive immunological tests for cancer diagnostics. Methods. Enzyme-linked immunosorbent assay and bioinformatics analysis. Results. Increased frequency of antibody response was found in sera of breast cancer patients to ZR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…In breast cancer, DNAJC2 can be considered as potential molecular marker in the sera of patients with breast cancer (16). Another study verified that depletion of DNAJC2 promotes endocrine resistance via deregulation of cell death and cell survival related pathways (16). All these findings are consistent with the present study which indicated DNAJC2 function as a cancer promotor.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In breast cancer, DNAJC2 can be considered as potential molecular marker in the sera of patients with breast cancer (16). Another study verified that depletion of DNAJC2 promotes endocrine resistance via deregulation of cell death and cell survival related pathways (16). All these findings are consistent with the present study which indicated DNAJC2 function as a cancer promotor.…”
Section: Discussionsupporting
confidence: 91%
“…Knockdown of DNAJC2 can strongly inhibit leukemia progression by obtaining command of genes related to retinoic acid (RA) by means of its connection with the RA receptor α and its binding to genes relevant to RA, both of which describe the mechanism of DNAJC2 in acute myeloid leukemia at the molecular level (14). In breast cancer, DNAJC2 can be considered as potential molecular marker in the sera of patients with breast cancer (16). Another study verified that depletion of DNAJC2 promotes endocrine resistance via deregulation of cell death and cell survival related pathways (16).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a previous study demonstrated that overexpression of DCAF13 in hepatocellular carcinoma is correlated with poor survival of patients ( 48 ). Dyachenko et al ( 49 ) demonstrated that KRR1 may represent a potential biomarker of particular histological types (invasive ductal) of breast tumor. Furthermore, Liu et al ( 50 ) revealed that HEATR1 can negatively regulate protein kinase B and further decrease resistance to gemcitabine and other chemotherapeutics.…”
Section: Discussionmentioning
confidence: 99%
“… 0.00055 [ 57 ] KRR1 Tumor-associated antigens KRR1 and ZRF1 and their cognate autoantibodies may be considered as potential molecular markers for breast cancer. 0.0318 [ 58 ] LUAD ATP6V0B miRNA-15a, which could regulate ATPase, H(+) transporting, lysosomal21 kDa, V0 subunit b(ATP6V0B), and miRNA-155, were found to be the most significant. 0.0188 [ 59 ] RIT1 The results provide a genome-wide map of oncogenic RIT1 functional interactions and identify components of the RAS pathway, spindle assembly checkpoint, and Hippo/YAP1 network as candidate therapeutic targets for RIT1 mutant lung cancer.…”
Section: Table A1mentioning
confidence: 99%